141k views
4 votes
Solve this quadratic Equation 3x^2 + 4x = 2

User Vaizki
by
5.3k points

1 Answer

5 votes

we know that for


a{x}^(2) + bx + c = 0

the roots are:


x1 = \frac{ - b + \sqrt{ { {b}^(2) } - 4ac} }{2a}

and


x2 = \frac{ - b - \sqrt{ { {b}^(2) } - 4ac} }{2a}

so putting into the formula we get:


3 {x}^(2) + 4x - 2 = 0

and


{{b}^(2) } - 4ac = {4}^(2) - 4 * 3 * ( - 2) = \\ 16 + 24 = 40

so:


x1 = ( - 4 + √(40) )/(2 * 3) = ( - 2 + √(10) )/(3)

and


x2 = ( - 4 - √(40) )/(2 * 3) = ( - 2 - √(10))/(3)

User Avner Levy
by
5.7k points